Surgical and Audiologic Comparison Between Sophono and Bone-Anchored Hearing Aids Implantation - Joong-Wook Shin; Sung Huhn Kim; Jae Young Choi; Hong-Joon Park; Seung-Chul Lee; Jee-Sun Choi; Han Q Park; Ho-Ki Lee (Clinical and Experimental Otorhinolaryngology, 2016)
Objectives Bone-anchored hearing aids (BAHA) occasionally cause soft tissue problems due to abutment. Because Sophono does not have abutment penetrating skin, it is thought that Sophono has no soft tissue problem relating to abutment. On the other hand, transcutaneous device’s output is reported to be 10 to 15 dB lower than percutaneous device. Therefore, in this study, Sophono and BAHA were compared to each other from surgical and audiological points of view. Methods We retrospectively reviewed the medical records of 9 Sophono patients and 10 BAHA patients. In BAHA cases, single vertical incision without skin thinning technique was done. We compared Sophono to BAHA by operation time, wound healing time, postoperative complications, postoperative hearing gain after switch on, and postoperative air-bone gap. Results The mean operation time was 60 minutes for Sophono and 25 minutes for BAHA. The wound healing time was 14 days for Sophono and 28 days for BAHA. No major intraoperative complication was observed. Skin problem was not observed in the 2 devices for the follow-up period. Postoperative hearing gain of bilateral aural atresia patients was 39.4 dB for BAHA (n=4) and 25.5 dB for Sophono (n=5). However, the difference was not statistically significant. In all patients included in this study, the difference of air-bone gap between two groups was 16.6 dB at 0.5 kHz and 18.2 dB at 4 kHz. BAHA was statistically significantly better than Sophono. Conclusion Considering the audiologic outcome, BAHA users were thought to have more audiologic benefit than Sophono users. However, Sophono had advantages over BAHA with abutment in cosmetic outcome. Sophono needed no daily skin maintenance and soft tissue complication due to abutment would not happen in Sophono. Therefore, a full explanation about each device is necessary before deciding implantation.